PENGARUH PEMBERIAN AROMATERAPI LAVENDER TERHADAP TINGKAT KECEMASAN PADA MASA PREMENOPAUSE DIDUSUN KAMPUNG BARU RT 04 DAN RT 05 DESA PURWOREJO KECAMATAN SENDURO KABUPATEN LUMAJANG - Fauziyah, Iin; Safitri, Rani; Purwati, Anik (NHM PRESS, 2024)
Premenopause is a transition period from the fertile period to the period of absence of fertilization. Most women will experience premenopausal symptoms at the age of 40 years, the peak is reached at the age of 50 years, when menopause occurs. Complaints experienced by premenopausal women will be very serious if not handled properly because they can cause changes that cause anxiety. Lavender aromatherapy can be an alternative for treating anxiety. This research aims to determine the effect of giving lavender aromatherapy on anxiety during the premenopausal period. The population in this study were premenopausal mothers aged 40-50 years in Hamlet Kampung Baru RT. 4 and RT. 5 Purworejo Village, Senduro District, Lumajang Regency with a sample of 25 premenopausal mothers using purposive sampling technique. Data collection uses a questionnaire sheet. Anxiety data was measured using HRS-A. Analysis of this research data used univariate and bivariate analysis. Bivariate data analysis using the Wilcoxon test. he research results showed that before being given lavender aromatherapy, 72% of respondents experienced moderate anxiety and after being given lavender aromatherapy, 60% of respondents did not experience anxiety. The results of the Wilcoxon test showed that there was an effect of giving lavender aromatherapy on anxiety levels during the premenopausal period in Kampung Baru RT. 04 and RT. 05 Purworejo Village, Senduro District, Lumajang Regency